Transformation of Digital-Based Fiqh Learning Methods to Improve Religious Literacy of Students at Rokan Hilir State Islamic Junior High School - Siti Halimah; Imran Rido; Laila Hamidah; Suci Oktaviani (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
The development of digital technology has significantly impacted the Islamic education system, including the learning of Islamic jurisprudence (fiqh) in Islamic schools (madrasahs). This study aims to analyze the transformation of digital-based fiqh learning methods and their impact on improving students' religious literacy at the State Islamic Junior High School (MTsN) in Rokan Hilir. This study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects included fiqh teachers, students, and the madrasah principal. The results show that the transformation of digital-based fiqh learning methods at MTsN Rokan Hilir was carried out through the integration of learning media such as Google Classroom, YouTube Edufiqih, Quizizz, and Canva for Education. The implementation of these media was able to shift students' learning paradigm from passive to active and encouraged an increased understanding of Islamic legal values. Students were more critical in exploring legal sources, discussing contemporary fiqh issues, and showed significant improvements in religious literacy. Teachers acted as facilitators and curators of digital content to ensure learning remained compliant with sharia principles. However, this study also identified several challenges, such as limited digital resources, gaps in internet access, and teachers' ability to master learning technology.